2017
DOI: 10.1088/1755-1315/70/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Development of a solar-powered electric bicycle in bike sharing transportation system

Abstract: Abstract. The increasing mobility has directly led to deteriorating traffic conditions, extra fuel consumption, increasing automobile exhaust emissions, air pollution and lowering quality of life. Apart from being clean, cheap and equitable mode of transport for short-distance journeys, cycling can potentially offer solutions to the problem of urban mobility. Many cities have tried promoting cycling particularly through the implementation of bike-sharing. Apparently the fourth generation bikesharing system has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…High: Up to tens of thousands € Medium: Hundreds to thousands of € * Low to medium: Hundreds of € * * According to estimations; ** dependent on charger and battery type; 1 according to references [2,17,19,20], based on average values for the sum of main pollutants: CO (carbon monoxide), NOx (nitrogen oxides), VOC (volatile organic compounds), and PM10 (particulate matter that have 10 micrograms per cubic meter or less in diameter); 2 according to reference [28]; 3 according to references [29,30]; 4 according to reference [26], based on average values for car/bus and e-bike, up to 5 km; 5 according to reference [21], based on average values; 6 according to references [31,32]; 7 according to reference [25]; 8 according to reference [33].…”
Section: Maintenance Costsmentioning
confidence: 99%
“…High: Up to tens of thousands € Medium: Hundreds to thousands of € * Low to medium: Hundreds of € * * According to estimations; ** dependent on charger and battery type; 1 according to references [2,17,19,20], based on average values for the sum of main pollutants: CO (carbon monoxide), NOx (nitrogen oxides), VOC (volatile organic compounds), and PM10 (particulate matter that have 10 micrograms per cubic meter or less in diameter); 2 according to reference [28]; 3 according to references [29,30]; 4 according to reference [26], based on average values for car/bus and e-bike, up to 5 km; 5 according to reference [21], based on average values; 6 according to references [31,32]; 7 according to reference [25]; 8 according to reference [33].…”
Section: Maintenance Costsmentioning
confidence: 99%
“…Moreover, the solar-powered e-bike sharing system includes zero CO 2 emissions and allows the reduction of the GHG emissions in urban areas. Adhisuwignjo et al (2017) developed a solar powered battery charging system for an e-bike, using a fuzzy logic algorithm for the design and testing of the controller system. Results showed that the specific algorithm that was designed could be used as a controller for the battery charging of the solar e-bike [6].…”
Section: E-bike Studiesmentioning
confidence: 99%
“…Adhisuwignjo et al (2017) developed a solar powered battery charging system for an e-bike, using a fuzzy logic algorithm for the design and testing of the controller system. Results showed that the specific algorithm that was designed could be used as a controller for the battery charging of the solar e-bike [6]. Apostolou et al (2018) studied the technical features and performance of solar-powered e-bikes, as well as various factors that affect users' satisfaction and their choices of a specific transportation mode [57].…”
Section: E-bike Studiesmentioning
confidence: 99%
See 2 more Smart Citations